Swelling of elastomers due to simulataneous diffusion of biodiesel and multi-axial large strain / Omid Kahbasi - Omid, Kahbasi (2013)
The concerns on depletion of petroleum-based fuel motivate the use of palm biodiesel as an alternative source of energy. However, the particular chemical composition of palm biodiesel affects significantly the performance of engineering components, in particularly elastomeric components. In this context, at least two important aspects contribute to the degradation of the elastomeric parts in service: diffusion of aggressive liquids leading to swelling and fluctuating multiaxial mechanical loading leading to fatigue failure. Hence, it is essential to understand the interactions between the two phenomena for durability analysis of the component. The present study investigates the swelling of elastomers due to diffusion of palm biodiesel in the presence of multiaxial large deformation and investigation on creep behavior of swollen elastomers. For this purpose, new experimental device and specimen are developed. The device consists of a hollow diabolo elastomeric specimen attached to specially-designed circular metallic grips and plates such that immersion tests can be conducted while the specimens are simultaneously subjected to various mechanical loadings: simple tension, simple torsion and combined tension-torsion. Thus, diffusion of liquids takes place in the material which concurrently undergoes multiaxial large deformation. Two types of elastomers are investigated: Nitrile Rubber (NBR) and Polychloroprene Rubber (CR). The particular features of the device and specimen are discussed and perspectives for further improvement are drawn. Keywords: Elastomer, palm biodiesel, swelling, multiaxial large strain, hydrostatic stress, creep, creep modulus